Cholesterol-Conjugated siRNA Accumulates in the Different Hematopoietic and Lymphoid Cells. - I.V., Chernikov; M.I., Meschaninova; A.G., Venyaminova; M.A., Zenkova; V.V., Vlassov; E.L., Chernolovskaya (Journal of Hematology and Oncology Research, 2016)
Small interfering RNA (siRNA) based drugs for overcoming multiple drug resistance of hematological malignancies could solve the problem of poor response to the chemotherapy and hight relapse rate. The main factor that significantly limits biomedical application of siRNA is inefficient delivery to target cells and tissues. The attachment of siRNA to molecules, which enter into the cell by natural transport mechanisms, can improve cellular uptake of siRNA. In current study the carrier-free cellular uptake of siRNA containig cholesterol residues conjugated to the 5’-end of the sense strand via oligomethylene linker of various length (here and after Ch-siRNA) was explored. The data demonstrate that cholesterol residue increase the accumulation of siRNA in all tested cell lines and the primary cells. The efficiency of Ch-siRNA accumulation in K562 cells depends greatly on the leangth of the linker connecting cholesterol and siRNA: Ch-siRNAs with linker of 10 - 12 methylene units accumulate the most efficiently in this cells. It was found that Ch-siRNA effectively accumulates in MOLT-3 (acute lymphoblastic leukemia, ALL), HL-60 (acute myelogenous leukemia, AML), K562 (chronic myelogenous leukemia CML) and primary peripheral blood mononuclear cells (PBMC) from patient with non-Hodgkin lymphoma (NHL) or healthy donor resulting in near 100% of transfected cell when used at 1 mM concentration.
Keywords: RNA interference; cholesterol-conjugated siRNA; acute lymphoblastic leukemia; acute myelogenous leukemia; chronic myelogenous leukemia; non-Hodgkin lymphoma